2020
DOI: 10.1038/s41598-020-60174-4
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Proton Conducting Electrolyte BaZr1-xHoxO3-δ (0.05 ≤ x ≤ 0.20) Ceramics for Intermediate Temperature Solid Oxide Fuel Cells

Abstract: In this study, the Ho-substituted BaZrO 3 electrolyte ceramics (BaZr 1-x Ho x o 3-δ , 0.05 ≤ x ≤ 0.20) were synthesized through a low-cost flash pyrolysis process followed by conventional sintering. The effects of Ho-substitution in BaZrO 3 studied in terms of the structural phase relationship, microstructure and electrical conductivity to substantiate augmented total electrical conductivity for intermediate temperature solid oxide fuel cells (IT-SOFCs). The Rietveld refined X-ray diffraction (XRD) patterns re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…12,13 However, the introduction of Y 3+ (r = 0.90 Å for 6-fold coordination) as a dopant reduces the tolerance factor down to 0.987 at 20% Y-doped BZO, leading to local distortions that can impede proton transport. 17 The sintering additives studied in the literature, with an ionic radius larger than Zr 4+ (r VI = 0.72 Å), such as Zn 2+ (r VI = 0.74 Å), Cu 2+ (r VI = 0.73 Å), Ho 3+ (r VI = 0.90 Å), or Ce 4+ (r VI = 0.87 Å), 22,44,45 are likely to have a detrimental impact on proton conductivity by reducing the tolerance factor even further. In contrast, the proposition of the smaller Mn 3+ ion (r VI = 0.64 Å), confirmed through our prior study, 25 has the potential to restore the BZY tolerance factor toward unity (Figure 1b).…”
Section: Comparison Ofmentioning
confidence: 99%
“…12,13 However, the introduction of Y 3+ (r = 0.90 Å for 6-fold coordination) as a dopant reduces the tolerance factor down to 0.987 at 20% Y-doped BZO, leading to local distortions that can impede proton transport. 17 The sintering additives studied in the literature, with an ionic radius larger than Zr 4+ (r VI = 0.72 Å), such as Zn 2+ (r VI = 0.74 Å), Cu 2+ (r VI = 0.73 Å), Ho 3+ (r VI = 0.90 Å), or Ce 4+ (r VI = 0.87 Å), 22,44,45 are likely to have a detrimental impact on proton conductivity by reducing the tolerance factor even further. In contrast, the proposition of the smaller Mn 3+ ion (r VI = 0.64 Å), confirmed through our prior study, 25 has the potential to restore the BZY tolerance factor toward unity (Figure 1b).…”
Section: Comparison Ofmentioning
confidence: 99%
“…Furthermore, our research group previously investigated Ho-doped BaZrO3 system and found 91.1% relative density for BaZr0.8Ho0.2O3-δ sintered at 1600 ℃ for 8 h with 1.11×10 -3 S-cm -1 total conductivity at 650 ℃ in 3% humidified atmosphere [25]. Similarly, Saini et al reported 99.1% relative density for spark plasma sintered BaZr0.8Ho0.2O3-δ with 9.64×10 -2 S-cm -1 total conductivity at 700 ℃ in 3% humidified atmosphere [26].…”
Section: Introductionmentioning
confidence: 99%
“…6 Designing efficient SSPC materials is crucial for advancing clean and renewable energy technologies and overcoming certain challenges related to conventional proton-conducting systems. 7,8 The current SSPC materials based on metalorganic frameworks (MOFs), [9][10][11][12] carbon-organic frameworks (COFs), [13][14][15][16] polymer electrolytes, [17][18][19] perovskite oxide, [20][21][22][23][24] etc. offer limited solution processability and the use of metal ions can lead to adverse environmental consequences and loss of activity upon leaching of metal ions.…”
Section: Introductionmentioning
confidence: 99%